PERANCANGAN DAN IMPLEMENTASI SISTEM PENDETEKSI DAN PERINGATAN KEBAKARAN BERBASIS IOT MENGGUNAKAN NODEMCU ESP8266 DAN SENSOR API - Gabriel Gracia Salindeho; Theophilus Wellem (Fakultas Teknologi Informasi, Universitas Kristen Satya Wacana, 2023)
Control and monitoring systems that use the Internet-of-Things (IoT) can be found in everyday life, for example, in smart home applications, smart transportation, and smart cities. IoT-based monitoring of environmental conditions both indoors and outdoors is generally carried out to reduce the risk of unwanted events. One example of an unwanted event is a fire. Fires can occur in houses, office buildings, rice fields, or forests. In order to help provide early warning of a flame that can cause a fire, this study aims to design and implement an IoT-based fire detection and warning system using the NodeMCU ESP8266 and a flame sensor. The sensor used is an infrared sensor that will detect infrared light radiation coming from a fire. The test results show that the system successfully detects the presence of fire up to 50 cm from the fire sensor and can be monitored via thinger.io. Additionally, notifications from thinger.io via e-mail and Telegram to users were successfully executed.